ANALISIS USABILITY MEDIA GAME-BASED LEARNING DALAM KONTEKS PEMBELAJARAN INFORMATIKA DAN PENGARUHNYA TERHADAP MOTIVASI BELAJAR SISWA SMP - Nurjihan Najma Zahera; Kartika Candra Kirana; Eko Tristyo Purwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Game-based educational tools have emerged as a key innovation designed to foster student participation and boost motivation. This research examines the influence of such media on the learning motivation of middle school students. A quantitative research design was applied using a quasi-experimental method. The findings reveal that the use of game-based media leads to a significant improvement in students’ learning motivation when compared to traditional teaching approaches. This type of media contributes to a more stimulating, interactive, and challenging educational environment. As such, incorporating game elements into instructional practices presents a promising approach to enhancing student motivation in the context of modern, digitally-driven education. Based on to the System Usability Scale (SUS), the usability score achieved was 71.15, indicates that Game-Based Learning media contributes positively to increasing student motivation.